Enhancing Data Security in Telemedicine IoT Applications through Hybrid Cryptography - Arasada Subashini; K. Nataraju (Current Research Progress in Physical Science Vol. 3, 2024)
IoT is a network of physical things or objects that are integrated with sensors, software, electronics, and network connectivity. By 2030, the total number of IoT devices is expected to reach 75.4 billion. With the aid of various medical sensors, a remote patient monitoring system will be designed for Internet of Things (IoT)-based telemedicine applications. With the aid of AI algorithms, the healthcare sensor data will eventually be identified and forecasted. In the current healthcare sector, a lot of sensitive data is exchanged. The integration of an increasing number of digital technologies in hospitals, together with laboratory and outpatient examinations of patients and their accompanying files, have all contributed to the growth of data related to patient care in recent years. Electronic health record systems are medical management systems that include all of a patient’s personal and medical data. As a consequence, this data must be stored and secured in the cloud. This paper describes a data storage and security solution that is well-suited for the Internet of Medical Things. The proposed model consists of a security framework for IoT-based telemedicine applications. Because of the shorter key length, the improved Elliptic Curve Cryptography (ECC) approach using Blake2 hashing takes substantially less time to encrypt. The data is encrypted with the created key and the Advanced Encrypted Standard (AES). The proposed security approach is a hybrid cryptography technique that combines symmetric and asymmetric key encryption, resulting in a more secure system.